Competências profissionais essenciais de um gestor de tecnologia da informação - Rinaldi, Maria Angélica (2017)
Information Technology (IT) has assumed a strategic role in organizations, and the IT Manager is mainly responsible for this positioning. New skills are necessary for this professional, of technical training, in order to promote the potentiality of IT. This is the purpose of the research: to investigate professional skills that emanate as essential of senior business managers for an IT Manager to make their area more strategic. On the theoretical basis, references were sought on IT and its strategic role and IT Manager Competencies, adopting Feeny and Willcocks (1998) model of essential IT capabilities, updated and applied from a resource perspective. The methodological strategy was based on case investigation through semi-structured interviews and content analysis, with 21 business executives surveyed. In the results, reflections on strategic IT are presented, emphasizing the importance of alignment with the need of the organization, fulfilling different roles and thus being a competitive advantage. The main contribution is presented as the competencies evidenced as essential for the IT Manager: (a) to have a business vision and act strategically; (b) take ownership of an innovative vision for IT and the business; (c) implement IT governance, aligned with the company's strategy; (d) to act in the performance management, ensuring availability and safety; (e) becoming a business and IT leader, involving people, being a facilitator and integrator; (f) building strong relationships with staff, suppliers, peers and leaders, sharing objectives, risks and benefits; (g) communicating well, with language close to the listener, being a "translator" between IT and business; (h) make conscious acquisitions of opportunities and needs; (i) to monitor established contracts; (j) facilitate hiring, aligning expectations and promoting partnerships; (k) develop suppliers that will enhance results for the company. It concludes with the proposal of re-presentation of the competencies model, inserting a new group of interpersonal relationships and the new competences of innovative vision and communication, emanated from the research. As practical collaboration and recommendations to the IT Manager, the first four competencies are also evidenced for their future, along with the other two: agility in decisions and continuous learning process. These, little explored in the literature, along with the other four, provide a new perspective of studies that trace back the essential professional competences for an IT Manager.